On the Dynamics of a Novel Liquid-Coupled Piezoelectric Micromachined Ultrasonic Transducer Designed to Have a Reduced Resonant Frequency and Enhanced Ultrasonic Reception Capabilities - Stephen Sammut; Edward Gatt; Ruben P. Borg (Micromachines, 2024)
This paper introduces a novel design for a liquid-deployed Piezoelectric Micromachined Ultrasonic Transducer (PMUT). This design was specifically developed to resonate at a lower ultrasonic frequency than a PMUT with a circular, fully clamped diaphragm with the same diameter. Furthermore, the novel design was also optimised to enhance its ultrasonic radiation reception capabilities. These parametric enhancements were necessary to develop a PMUT device that could form part of an eventual microscale sensory device used for the Structural Health Monitoring (SHM) of reinforced concrete (RC) structures. Through these two enhancements, an eventual microscale sensor can be made smaller, thus taking up a smaller die footprint and also be able to be deployed further apart from each other. Eventually, this would reduce the developed distributed sensor system’s cost. The innovative design employed a configuration where the diaphragm was only pinned at particular points along its circumference. This paper presents results from Finite Element Modelling (FEM), as well as experimental work that was conducted to develop and test this novel PMUT. The experimental work presented involved both laser vibrometry and ultrasonic radiation lab work. The results show that when compared to a clamped diaphragm design, the novel device managed to achieve the required reduction in resonant frequency and presented an enhanced sensitivity to incoming ultrasonic radiation.